2017
DOI: 10.1007/s10787-017-0419-z
|View full text |Cite
|
Sign up to set email alerts
|

TMEM88 mediates inflammatory cytokines secretion by regulating JNK/P38 and canonical Wnt/β-catenin signaling pathway in LX-2 cells

Abstract: Recent data have shown that Transmembrane protein 88 (TMEM88), a newly discovered protein localized on the cell membrane, interacts with the PDZ domain of disheveled-1 (Dvl-1) in Xenopus embryos. Indeed, TMEM88 might inhibit the canonical Wnt/β-catenin signaling pathway by competing with LRP5/6 for interaction with Dvl-1. TMEM88 plays a crucial role in regulating human stem cell differentiation and embryonic development. Until recently, the function of TMEM88 has been a matter of debate. In this study, we expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Moreover, TMEM88 inhibits Wnt/β‐catenin signaling by enhancing the localization of the β‐catenin‐containing Wnt signalosome to multivesicular bodies, a change that impedes β‐catenin nuclear translocation [24] . Previous studies have shown that TMEM88 exerts its function in various cellular processes via regulation of Wnt/β‐catenin signaling [5‐7,9] . Interestingly, a recent study has revealed that TMEM88 plays the tumor‐suppressive role in thyroid cancer via inhibition of Wnt/β‐catenin signaling [23] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, TMEM88 inhibits Wnt/β‐catenin signaling by enhancing the localization of the β‐catenin‐containing Wnt signalosome to multivesicular bodies, a change that impedes β‐catenin nuclear translocation [24] . Previous studies have shown that TMEM88 exerts its function in various cellular processes via regulation of Wnt/β‐catenin signaling [5‐7,9] . Interestingly, a recent study has revealed that TMEM88 plays the tumor‐suppressive role in thyroid cancer via inhibition of Wnt/β‐catenin signaling [23] .…”
Section: Discussionmentioning
confidence: 99%
“…Although the studies of TMEM88 are limited, the involvement of TMEM88 in multiple pathological processes has been increasingly highlighted. The decreased expression of TMEM88 contributes to progression of hepatic fibrosis, with an effect on the activation of hepatic stellate cells [6,7] . Elevation of TMEM88 leads to an increase in the secretion of inflammatory factors in alcoholic liver disease [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Human pro-monocytic cells U937 cell line was used as a source of inflammatory response cell [46,47]. U937 cell line was resuspended in a Dulbecco’s modified Eagle’s medium (DMEM) 1 g/L D-glucose (Gibco, Life Technologies, Milan, Italy) supplemented with 10% v/v heat-inactivated fetal bovine serum (FBS) (Invitrogen, Carlsbad, CA, USA), 1% penicillin/streptomycin (Carlo Erba, Milan, Italy) antibiotic/antimycotic solution, and 60 mg/mL of gentamicin (Gibco, Monza, Italy).…”
Section: Methodsmentioning
confidence: 99%
“…[7][8][9][10] Notably, activation of HSCs is connected with several inflammatory cytokines, such as IL-6 and IL-1β. 11 It is particularly important to find an effective way to inhibit the expression of macrophages. Lipopolysaccharide (LPS) is the main component of the cell wall of gram-negative bacteria and the level of it is elevated in patients with alcoholic fatty liver or cirrhosis.…”
Section: Introductionmentioning
confidence: 99%